Bogdan Petriceicu Hasdeu și spiritul său civic - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2026)
The article explores the civic spirit of Bogdan Petriceicu Hasdeu, as reflected in his journalistic work, particularly in the satirical magazine „Aghiuță” and the political article „YES or NO”. Hasdeu advocated democratic reforms and universal suffrage, criticizing corruption and societal apathy. His ideas are examined in comparison to current political realities in the Republic of Moldova, highlighting the ongoing need for civic participation and inclusive democracy. The article also contrasts Hasdeu’s profound journalism with the often superficial communication of the digital era.